LANGUAGE AND GENDER IN PUBLIC SPACE: AN APPLIED LINGUISTIC STUDY OF INCLUSIVE LANGUAGE USE - Samuel Nugraha Cristy; Junaidi (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2025)
This study investigates the intersection of language and gender as represented in public spaces, focusing on the presence, absence, and patterns of inclusive language use. Drawing upon the framework of applied linguistics and critical discourse analysis, this research explores how public signage—across institutions, commercial areas, and communal facilities—embeds gender ideologies and either reinforces or challenges binary norms. Data were collected through a qualitative field survey and visual documentation of public signs in various domains, and analyzed thematically to identify linguistic patterns related to gender representation. The findings reveal that gender-exclusive and male-default language continues to dominate public communication in most observed settings, indicating a widespread lack of awareness or commitment to gender-inclusive principles. Phrases such as “he/she,” binary restroom labels, and job titles with marked gender (e.g., “chairman,” “saleswoman”) are still prevalent, subtly perpetuating the notion of gender essentialism. However, a minority of signs—particularly in educational institutions and certain private sectors—demonstrate emerging inclusive strategies, including the use of gender-neutral terms, inclusive pronouns (e.g., “they”), and visual symbols representing diverse gender identities. These instances signal a gradual shift in public language practices, albeit fragmented and inconsistently applied. This study affirms that public language functions not merely as a communicative tool, but as a site of ideological struggle where power relations and social norms are negotiated. As such, it carries significant implications for inclusive policy development, language planning, and sociolinguistic awareness campaigns. The research also highlights the need for institutional guidelines and educational initiatives to support more equitable and inclusive language use in public signage. Ultimately, this work contributes to a broader understanding of how inclusive linguistic practices in public space can promote social recognition, reduce marginalization, and foster a more inclusive society